2014
DOI: 10.4314/jae.v17i2.17
|View full text |Cite
|
Sign up to set email alerts
|

Attitude of farmers towards Non-Governmental Extension Organisations in Oyo-State, Nigeria

Abstract: The study examined the attitude of farmers towards non-governmental extension organisations (NGEOs)

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

1
0
0

Year Published

2018
2018
2018
2018

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 4 publications
(3 reference statements)
1
0
0
Order By: Relevance
“…The personal characteristics of the respondents are presented in Table 1, which reveals that the mean age of the respondents was 44.2. This implies that most of the respondents were still in their active years and it is in consonance with the findings of Tijani and Mudashir (2013), who reported crop farmers in Oyo state to be either young or middle-aged and in their active years. The table further revealed that 74.1% of the respondents were males while 25.6% of them were females, implying that the farming population in the study area is still male-dominated.…”
Section: Resultssupporting
confidence: 87%
“…The personal characteristics of the respondents are presented in Table 1, which reveals that the mean age of the respondents was 44.2. This implies that most of the respondents were still in their active years and it is in consonance with the findings of Tijani and Mudashir (2013), who reported crop farmers in Oyo state to be either young or middle-aged and in their active years. The table further revealed that 74.1% of the respondents were males while 25.6% of them were females, implying that the farming population in the study area is still male-dominated.…”
Section: Resultssupporting
confidence: 87%